Functionalization of polyesters with multiple B vitamins. Issue 19 (16th July 2017) - Soxman, Andrew G.; DeLuca, Jenna M.; Kinlough, Kylie M.; Iwig, David F.; Mathers, Robert T.
ABSTRACT: A method to covalently attach combinations of six different B vitamins provided an avenue to new functional thermosets without multi‐step coupling reactions. The melt polymerization strategy required no organic solvent and facilitated covalent attachment of OH (B1, B2, B5, B6 ) or COOH (B7, B9 ) groups on B vitamins via Fischer esterification. Characterization of model reactions with LC/MS, FTIR, and GPC confirmed covalent attachment. Based on control experiments, B vitamins demonstrated unexpected thermal stability and appreciable solubility in the melt polymerization. This approach was demonstrated with citric acid and diglycerol, but has wide‐ranging potential for other polar monomers with negative octanol–water partition coefficients (LogP). © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 3308–3316 Abstract : Combinations of six B vitamins provide new functional thermosets. Fischer esterification facilitates covalent attachment of B vitamins with polyols and citric acid in a single step.